Fast moving consumer goods (FMCG) market in Romania: Features and trends - Silvius Stanciu; Florina Oana Virl\~anut\~a; Oana Alexandra Vochin; Victor-Romeo Ionescu; Valentin Marian Antohi (Amfiteatru Economic Journal, 2019)
The development of the fast-moving consumer goods market in Romania, disputed by European companies specialized in retail, is a spectacular phenomenon, which exceeded the forecasts of the specialists and the expectations of the investors. European integration and adherence to Western security systems gave the specialized companies, with foreign capital, the security they needed in order to carry out consistent investments. The paper proposes a presentation and analysis of the development of modern means of commerce specific to the fast-moving consumer goods' sector in our country. The bibliographic documentation was made using specialized sources and specialized articles from well known scientific databases. The assessment of the degree of concentration of the fast-moving consumer goods market based on the Gini Struck Method has led to a high value of the index, which shows the dominance of large economic agents at national level. The fierce competition has forced the companies in the sector to develop commercial areas, to innovate sales techniques, to identify new market niches, or even social responsibility actions. The forecasts for the development of the sector are optimistic, but the operators have to identify new means for consolidating or increasing the market position. The paper has an applicative character, being especially useful to consumers and the business environment.
Keywords: L11; L66; Q18; 330; fast moving consumer goods (FMCG) market; Struck Gini Index; concentration; Romania